Ibu mertuaku - P. Ramlee, Tan Sri, 1929-1973
Kassim Selamat, a talented saxophonist with a golden voice, was naturally adored by female fans. One fan, Sabariah Mansoor, made a courageous effort to meet him in person. It was love at first sight for both of them. When Sabariah's mother, Nyonya Mansoor, found out that she wanted to break her relationship with her fiancee, Doktor Ismadi, she was furious. And matters was made worst since Kassim Selamat was a musician. They got married and left Singapore for Penang thinking of starting life anew. When Sabariah was pregnant, Nyonya Mansoor took Sabariah back to Singapore and sent a false telegram to Kassim stating Sabariah has passed away while giving birth. Kassim was devastated and cried night and day till he lost his vision and became blind. He was taken in by a kind hearted lady. Mamak Maidin heard Kassim playing the saxophone and suggested that they tour the whole of Malaysia. In the meantime, Sabariah got married to Doktor Ismadi. She persuaded her husband to operate on Kassim's blind eyes. Was the operation successful? What did Kassim do when he realised that Sabariah is alive all this while? Did Nyonya Mansoor managed to lie her way through again?